Reframing ICT Adoption in Agricultural Extension: Introducing the AWN Theory as a Socio-Rational Model for Digital Transformation - Andi Warnaen; Nurlaili Nurlaili; Yoyon Haryanto; Ugik Romadi (Jurnal Agrisistem: Seri Sosek dan Penyuluhan, 2026)
The rapid digitalization of agriculture has transformed how knowledge, innovation, and extension services operate across developing economies. This study aims to systematically examine how Information and Communication Technologies (ICTs) enhance agricultural extension, focusing on their role in fostering inclusion, innovation, and productivity. Using the Systematic Literature Review (SLR) method guided by PRISMA standards, 46 peer-reviewed articles indexed in Scopus (2015–2025) were analyzed through bibliometric mapping and thematic synthesis. The findings reveal that ICT adoption in agricultural extension functions as a socio-rational process, driven by the interaction of three dimensions: rational decision-making (micro level), relational diffusion and trust (meso level), and institutional governance (macro level). Notably, the review develops the AWN Theory (Actor–Work–Network Theory of Rational Integration) and its operational model, the AWN-TORI Framework, to integrate behavioral, relational, and structural paradigms. These frameworks explain how the alignment among cognitive, social, and institutional mechanisms leads to sustained ICT adoption and farmer empowerment. However, the results also indicate persistent challenges related to infrastructure, digital literacy, and gender disparities, especially in resource-limited regions. The study concludes that effective digital transformation in agriculture requires inclusive, adaptive, and context-specific ICT models. Future research should empirically test the AWN Theory through longitudinal and mixed-method approaches while exploring how emerging technologies such as AI, IoT, and blockchain interact within agricultural innovation systems.